Answer:
x=2,y=-6,z=-1
Explanation:
Hello, I think I can help you
Let
equation 1 (1) 4x-16z=24
equation 2 (2) 2x-3y-3z=25
equation 3 (3) 2x+2y-3z=-5
equation 4 (4) 4x+2y+2z=-6
to eliminate x and z , we can do
(2)-(3)
2x-3y-3z=25
-(2x+2y-3z=-5)
____________
0-5y-0 =30
-5y=30
divide each side by -5
-5y/-5=30/-5
y=-6
to eliminate y , we can do
(3)-(4)
2x+2y-3z=-5
-(4x+2y+2z=-6)
___________
-2x+0-5z=1 equation (5)
Now, to eliminate z do, (1)+2*(5)
(1) 4x-16z=24
2*(5)=-4x-10z=2
(1)+2*(5)
4x-16z=24
-4x-10z=2
_________
0-26z=26
-26z=26
z=26/-26
z=-1
from (1) isolating x
4x-16z=24
4x=24+16z
x=6+4z
x=6+4(-1)
X=2
have a great day